(untitled) (Global Journal of Human-Social Science, 2022)
We present the results of a study to contribute to the reflections and discussions about the formative processes for teaching in the post-pandemic context To this end we conducted a piece of research constituted by a corpus formed out of 13 pedagogical letters sent to an event that took place in June 2022 by teachers who work in schools and carry out strict sensu postgraduate studies